Pelatihan Manajemen Keuangan Bagi Pelaku Usaha Mikro Kecil dan Menengah (UMKM) Olahan Pangan - Darnilawati, Darnilawati; Hasanah, Nur; Jenita, Jenita; Alchudri, Alchudri (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
MSMEs that develop become economic pillars that are able to survive the economic crisis and can provide employment opportunities so that they can increase economic growth. For this reason, neat and correct financial management is needed. The aim of this activity is to increase knowledge and understanding of financial management for food processed MSMEs in the Tampan Pekanbaru sub-district, and provide direct training to create good and correct financial management. The methods used are lectures, discussions, practice and evaluation of success. The results of the activity stated that participants were very enthusiastic about taking part in the training so that they could increase their knowledge and understanding regarding financial management and were motivated to practice financial management in their business operational activities. They know the importance of financial management which provides information on financial health conditions which are used as a basis for making decisions regarding financial problems.